Risk Management for Italian Non‐Financial Firms: Currency and Interest Rate Exposure. (8th August 2012) - Bodnar, Gordon M.; Consolandi, Costanza; Gabbi, Giampaolo; Jaiswal‐Dale, Ameeta
Abstract This paper surveys risk management practices among Italian non‐financial firms. This paper's contribution lies in investigating derivative usage particular to Italian businesses, a group whose public disclosure of derivative instruments is not routine. Italy is characterised by a high percentage of small and medium sized family run firms. The survey examines determinants of currency and interest rate derivative use with respect currency and to firm size, geographical location, rating, industry, access to capital markets and educated management. The results from the logistic regressions suggest that Italian non‐financial firms' use of derivative contracts is strongly influenced by these characteristics.